Women’s Empowerment as It Relates to Attitudes Towards and Practice of Female Genital Mutilation/Cutting of Daughters: An Ecological Analysis of Demographic and Health Surveys From 12 African Countries - Coll, Carolina V. N.; Santos, Thiago M.; Wendt, Andrea; Hellwig, Franciele; Ewerling, Fernanda; Barros, Aluisio J. D. (Frontiers in Sociology, 2022)
Background Women’s empowerment may play a relevant role in shaping attitudes towards female genital mutilation (FGM) practices. We aimed to investigate how empowerment may affect women´s intention to perpetuate FGM and the circumcision of their daughters in African countries. Materials and methods We used data from Demographic and Health Surveys carried out from 2010 to 2018. The countries included in our study were Benin, Burkina Faso, Chad, Côte d´Ivoire, Ethiopia, Guinea, Kenya, Mali, Nigeria, Senegal, Tanzania, and Togo. This study included 77,191 women aged 15-49 years with at least one daughter between zero and 14 years. The proportion of women who reported having at least one circumcised daughter (outcome) as well as the mother’s opinion towards FGM continuation were stratified by empowerment levels in three different domains (decision-making, attitude to violence and social independence) for each country. We also performed double data disaggregation to investigate how the intersectionality between both indicators would affect the outcome. Results The prevalence of at least one circumcised daughter was consistently higher among low empowered women. Tanzania, Benin, and Togo were exceptions for which no differences were observed in none of the three domains of empowerment. The double data disaggregation pointed to a lower proportion of daughters’ circumcision among women against the continuation of FGM and with a high empowerment level while a higher proportion of daughters’ circumcision was observed among women in favor of FGM and with a low empowerment level in most countries. This pattern was particularly evident for the social independence domain of empowerment. Conclusion Improvements in women´s empowerment and shifts in social norms are key to achieve significant reductions in FGM.